2011
DOI: 10.4172/2157-7110.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Treatment On Physical and Functional Properties of Orange (Citrus Sinensis) Peel and Leaves

Abstract: NomenclatureK, n: Page Model constants; r: Coefficient of Correlation; SE: Standard Error; P: Relative Percent Error (%); t: Time; X r: : Reduced moisture content; X 0 : Initial moisture content (kg water/kg db); X f : Final moisture content (kg water/kg db); R r : Reduced drying rate; N: Numbers of data points; n p : Numbers of parameters SubscriptsCal: Calculated; exp: Experimental; j: Samples number. Material and Methods MaterialFresh oranges (Citrus sinensis) and leaves of "Maltaise" variety were picked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
(29 reference statements)
3
19
1
Order By: Relevance
“…In fact, the absorption of microwaves into the particle led to moisture evaporation which increased the water vapor pressure within the particle and resulted in an additional moisture transfer mechanism to the particle surface (Horuz et al, 2017). The results found in the present study are in agreement with those reported by previous studies that focused on microwave drying of other vegetables such as orange peels (Ghanem, Mihoubi, Kechaou, & Boudhrioua Mihoubi, 2012;Kammoun Bejar, Kechaou, & Boudhrioua Mihoubi, 2011), onion slices (Arslan & Özcan, 2010), spinach (Ozkan, Akbudak, & Akbudak, 2007), kiwi fruit (Maskan, 2001), carob by-product (Tounsi, Karra, Kechaou, & Kechaou, 2017), and bitter gourd slices (Nalawade et al, 2018).…”
Section: Microwave Dryingsupporting
confidence: 93%
“…In fact, the absorption of microwaves into the particle led to moisture evaporation which increased the water vapor pressure within the particle and resulted in an additional moisture transfer mechanism to the particle surface (Horuz et al, 2017). The results found in the present study are in agreement with those reported by previous studies that focused on microwave drying of other vegetables such as orange peels (Ghanem, Mihoubi, Kechaou, & Boudhrioua Mihoubi, 2012;Kammoun Bejar, Kechaou, & Boudhrioua Mihoubi, 2011), onion slices (Arslan & Özcan, 2010), spinach (Ozkan, Akbudak, & Akbudak, 2007), kiwi fruit (Maskan, 2001), carob by-product (Tounsi, Karra, Kechaou, & Kechaou, 2017), and bitter gourd slices (Nalawade et al, 2018).…”
Section: Microwave Dryingsupporting
confidence: 93%
“…However, it was also found that the highest retention level of TPC was 22.80% when drying at 300 W. This may be because of the combined effect of both shorter drying time and a mild thermal application of 300 W, which helped to retain phenolic compounds otherwise lost during the drying process. In contrast, Kammoun Bejar, Kechaou, and Boudhrioua Mihoubi () found that drying with microwaves at a power of 450 W significantly improved the extraction of TPC from citrus peel. According to these authors, at this MP, the structure of the fiber matrix become larger and looser and thereafter helped facilitate extraction with solvent.…”
Section: Resultsmentioning
confidence: 93%
“…Inchuen et al () have reported that increasing MP from 180 to 540 W resulted in an increase of the TPC of Thai red curry powder. Kammoun Bejar et al () found that the drying method deeply affected qualitative phenolic composition by increasing contents of some compounds but decreasing those of others, as well as by the appearance of some other phenolics such as transcinnamic acid and 4′,5,7‐trihydroxyflavone while other phenolic compounds were lost. In the drying treatment of plants, according to Mueller‐Harvey (), heating not only deactivates enzymes, but also degrades phytochemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, preliminary studies showed that the factors that most influenced the functional properties of DF when ethanol treatment was used along with microwave drying for its obtention, were ethanol/sample ratio and drying temperature (Sette, Latorre, Soria, de Escalada Pla, & Gerschenson, 2011). Microwave drying also has been contemplated in the drying up process of carrots pomace and of oranges peel and leaves according to Bejar, Kechaou, and Mihoubi (2011) and Hern andez-Ortega, Kissangou, NecoecheaMondrag on, S anchez-Pardo, and Ortiz-Moreno (2013) respectively. In the literature there is no study, to our knowledge, analysing the effect of ethanol treatment step combined with microwave drying when they are applied for the obtention from Prunus persica of fractions enriched in dietary fibre.…”
Section: Introductionmentioning
confidence: 99%